Transitional criminal justice in post-dictatorial and post-conflict societies / edited by Agata Fijalkowski, Raluca Grosescu. - Fijalkowski, Agata; Grosescu, Raluca (Series on transitional justice ;, 2015)
This volume considers the important and timely question of criminal justice as a method of addressing state violence committed by non-democratic regimes. The book's main objectives concern a fresh, contemporary, and critical analysis of transitional criminal justice as a concept and its related measures, beginning with the initiatives that have been put in place with the fall of the Communist regimes in Europe in 1989.The project argues for rethinking and revisiting filters that scholars use to interpret main issues of transitional criminal justice, such as: the relationship between judicial accountability, democratisation and politics in transitional societies; the role of successor trials in rewriting history; the interaction between domestic and international actors and specific initiatives in shaping transitional justice; and the paradox of time in enhancing accountability for human rights violations. In order to accomplish this, the volume considers cases of domestic accountability in the post-1989 era, from different geographical areas, such as Europe, Asia and Africa, in relation to key events from various periods of time. In this way the approach, which investigates space and time-lines in key examples, also takes into account a longitudinal study of transitional criminal justice itself. About the book'Transitional justice nowadays is an industry which produces hundreds of texts each year and it is difficult to turn our attention to an intellectual product. This book is well-balanced and will find recognition in readers and students of transitional justice, as well as researchers on social transformation. It is a collection in the best tradition of socio-legal research. The book is recommended for two reasons: its serious treatment of criminal justice as a part of transitional justice, and its approach, which locates the problem of transitional justice in post-communist Europe in a broader, comparative context.' Prof. Dr. Adam Czarnota, Scientific Director of the International Institute for the Sociology of Law, Oati, Spain'By carefully considering how criminal justice relates to democratization, collective memory, internationalist concerns, and the passage of time since violations occurred, this volume contributes importantly to the evolving transitional justice literature. The questions it raises are timely and theoretically grounded, and the choice of cases diverse and illuminating. Its authors richly contextualize their examinations, complementing recent broad comparative studies that explore large numbers of cases with little detail. This in-depth study critically advances our understanding of the challenges of justice on the fraught terrain of transitioning societies.' Nadya Nedelsky, Associate Professor and Chair, International Studies, Macalester College, Saint Paul, MN.'A collection of provocative, thoughtful and superbly documented contributions to our understanding of the dilemmas of transitional justice in post-dictatorial societies. The authors argue that democratic communities cannot function properly if they do not address past crimes and abuses. Genuine reconciliation cannot take place if memory and justice are ignored and denied. With its insightful comparative perspective, this book is highly recommended to all those who care about the relationship between human rights and democracy.' Vladimir Tismaneanu, University of Maryland (College Park)